Synthesis of ω-vinyl methacrylic polymers via in situ catalytic chain transfer polymerisation for photopolymer additive manufacturing applications - Sefton, Joseph (2024)
Photopolymer-based additive manufacture (PAM) typically relies on the use of crosslinking acrylate monomers, with very little existing literature on PAM of thermoplastics. New materials and understanding of the polymerisation that occurs in PAM is key to enabling further advancement toward PAM of thermoplastics. In this work, ω-vinyl polymers were utilised as chain transfer agents (CTAs) in digital light projection (DLP) of thermoplastic parts in order to gain an understanding of the empirical polymer characteristics required for successful thermoplastic PAM.